Landslide Science for a Safer Geoenvironment Volume 3: Targeted Landslides - Sassa, Kyoji; Canuti, Paolo; Yin, Yueping (Springer International Publishing : Imprint: Springer, 2014)
This volume contains peer-reviewed papers from the Third World Landslide Forum organized by the International Consortium on Landslides (ICL) in June 2014. The complete collection of papers from the Forum is published in three full-color volumes and one mono-color volume. This third full-color volume contains the following:   ·        Debris flows ·        Rock-slope instability and failure ·        Earthquake-induced landslides ·        Rain-induced landslides ·        Landslides in cultural/natural heritage sites ·        Urban landslides ·        Landslides in cold regions ·        Landslides in coastal and submarine environments ·        Natural dams and landslides in reservoirs.